Trento, which kind of future? Perspectives for a resilient city - Matteo Aimini (Agathón)
Cities and their surroundings are excellent case studies and inexhaustible testing grounds as they require constant adaptations and revisions; mutable environments where it is possible to experiment new approaches and paradigm changes, in order to demonstrate that it is possible to turn the direction towards less disturbing and more profitable scenarios from the environmental and socio-economic standpoints. In this sense, the research task of the Trento Urban Transformation Research Unit (TUT) is to review the perspectives of the Trento Urban Plan according to public and private stakeholder, to record and propose alternative scenarios towards a more Resilient direction. Among the challenges that the Strategic Plan need to address there is a specific category devoted to the performative outlook of the city concerning the ecological imprinting. This category includes strategies for landscape design approaches capable of tackling the challenges posed by our contemporary era.